Interaction of Work Culture and Transformational Leadership in Encouraging Employee Performance at APT3B Banten Province - Wiguna, Wahyu; Yusnita, Nancy; Sunaryo, Widodo (Journal of Public Representative and Society Provision, 2024)
Human Resource Management (HRM) plays an important role in this study, as it focuses on managing high-performing employees in APT3B. A harmonious work culture and transformational leadership are closely related to MSDM practices, which support employee development and create a productive work environment. Through good MSDM, organizations can effectively manage cultural and leadership values, which leads to improved employee performance and engagement. This study aims to analyze how the interaction between work culture and transformational leadership can affect employee performance in APT3B Banten Province. A work culture that supports collaboration and open communication is believed to be able to create a harmonious work environment, while transformational leadership that cares about the well-being of employees can increase their motivation and commitment. This study uses a qualitative method with a case study approach. Data was obtained through in-depth interviews and observations of employees and managers in APT3B. Thematic analysis is used to identify the influence of work culture and transformational leadership on employee performance. The results of the study show that these two factors interact with each other and contribute to improving employee morale, commitment, and performance. A harmonious work culture, supported by leadership that cares about employee development, has been shown to increase productivity and overall organizational success.